Strategic Development and Innovation Strategies in Uzbekistan’s Tourism Industry: Conceptual and Methodological Approaches - Turdibekov Khasan Ibragimovich (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Tourism is a key driver of economic growth, job creation, and regional development, and Uzbekistan has recently emerged as a dynamic participant in this sector. Specific Background: Despite notable progress in infrastructure development and heritage promotion, challenges remain in integrating sustainability and innovation into Uzbekistan’s tourism framework. Knowledge Gap: Limited empirical research has analyzed how strategic development and innovation contribute to tourism competitiveness in the Uzbek context. Aims: This study aims to evaluate Uzbekistan’s tourism development strategies, identify innovation practices, and assess performance through indicators such as the Travel & Tourism Development Index (T&T DI), international receipts, and service exports. Results: Findings reveal consistent growth in the T&T DI (from 3.41 in 2019 to 3.68 projected in 2024), alongside rising international tourism receipts and expenditures. However, gaps persist in sustainability and infrastructure, necessitating eco-tourism and technology-driven solutions. Novelty: The study integrates benchmarking and mixed-method analyses to connect strategic reforms with innovation and sustainability outcomes. Implications: Results underscore the importance of aligning national tourism strategies with global best practices by embedding green technologies, digital innovation, and human capital investment to enhance long-term competitiveness and sustainable growth in Uzbekistan’s tourism sector.Highlight : The study emphasizes strategic and innovative approaches to enhance Uzbekistan’s tourism competitiveness. Sustainable practices and technological integration are identified as key drivers for long-term growth. Findings highlight the importance of policy reforms and infrastructure investment to strengthen global positioning. Keywords : Tourism Development, Innovation Strategies, Sustainability, Uzbekistan, Competitiveness